Psychological narcissism and its contribution to the feeling of psychological loneliness among young basketball players - Hashem , Mariam (Journal of Physical Education, 2024)
This study aimed to determine the degree of psychological narcissism and the experience of psychological loneliness among young basketball players. It also sought to establish the relationship, contribution, and impact of psychological narcissism on the experience of psychological loneliness among young basketball players. The researcher hypothesizes that psychological narcissism and psychological loneliness among players have a moral correlation. The study focused on youth basketball and utilized a descriptive approach modeled on co-relational relationships. The community consisted of basketball players from Baghdad youth clubs who were training to participate in the local sports season (2023/234). The Sulaikh Club, Housing, and Industries naturally distributed the remaining 72 players among themselves. We intentionally selected Electricity, Air Force, and Civil Defense players using a thorough enumeration approach, ensuring 100% participation. They were considered a single sample, with 35 players selected for the construction sample, accounting for 48.611%, and 5 players selected for other purposes. Intentional gamers from this group made up 6.944% of the exploratory sample and 44.4444% of the remaining 32 individuals in the main research sample. We constructed specialized scales, such as paper and pen scales, to measure two phenomena within the target sample. We developed these scales by following field methodological steps and applying statistical treatments to the building sample. We obtained the results by conducting a survey and scanning the main sample. We then analyzed the results using the SPSS system. The findings indicate that young players exhibit a significant degree of psychological narcissism in the training and competitive setting, as well as a reduced sense of psychological unity in their basketball performances. The manifestation of these psychological phenomena in a partnership has a detrimental impact on the character of their group game. The suggestions were to focus on preventing and reducing psychological narcissism among basketball players. They should strive to enhance their self-confidence and assume responsibility for confronting the various situations in which they encounter psychological stress. This will help to establish a sense of psychological unity, which in turn positively impacts the outcomes of their competitions in this collaborative game that demands cooperation among the players.